Subjective and Objective Olfactory Abnormalities in Crohn's disease - Fischer, Marie; Zopf, Yurdagül; Elm, Cornelia; Pechmann, Georg; Hahn, Eckhart Georg; Schwab, Dieter; Kornhuber, Johannes; Thürauf, Norbert (Chemical Senses, 2014)
The pathogenesis of Crohn's disease (CD) is still unknown, but the involvement of the olfactory system in CD appears possible. No study to date has systematically assessed the olfactory function in CD patients. We investigated the olfactory function in CD patients in active (n = 31) and inactive disease (n = 27) and in a control group of age- and sex-matched healthy subjects (n = 35). Subjective olfactory testing was applied using the Sniffin' Sticks test. For olfactory testing, olfactory event-related potentials (OERPs) were obtained with a 4-channel olfactometer using phenyl ethyl alcohol (PEA) and hydrogen sulfide (H2S). Carbon dioxide (CO2) was employed as control stimulus, and chemosomatosensory event-related potentials (CSSERPs) were registered. Results of the Sniffin' Sticks test revealed significantly different olfactory hedonic judgment with increased olfactory hedonic estimates for pleasant odorants in CD patients in active disease compared with healthy subjects. A statistical trend was found toward lower olfactory thresholds in CD patients. In objective olfactory testing, CD patients showed lower amplitudes of OERPs and CSSERPs. Additionally, OERPs showed significantly shorter N1- and P2 latencies following stimulation of the right nostril with H2S in CD patients in inactive disease compared with controls. Our study demonstrates specific abnormalities of olfactory perception in CD patients.
EVALuna2:1836